University students' self-presentation on Tiktok in the context of group communication - Arianto Arianto (Jurnal Studi Komunikasi, 2024)
The phenomenon of self-presentation is increasingly trending to reveal, develop identities, manipulate and customise individuals' self-images on social media. University students present themselves on TikTok through video uploads, music, and distributed using TikTok's highly personalised algorithms in group communication: watch history, re-watches, likes, comments, and post-view activity. We present the concept of online impression management through the lens of self-presentation theory as the practice of conveying self-impression and controlling personal information to represent one's self-image to be liked. This study uses a qualitative approach, uses phenomenological methods to find the meaning and interpretation of self-presentation through uploads on TikTok. They expressed personal information to their reference group and experimented based on different roles when constructing identity. Some strategies are used to give a positive impression to their friends. They projected different versions of themselves depending on self-category and group communication context when receiving positive feedback or likes.